The plainsman [videorecording (DVD)] - Cooper, Gary, 1901-1961; Arthur, Jean, 1900-1991; Bickford, Charles, 1891-1967; DeMille, Cecil B. (Cecil Blount), 1881-1959; DeMille, Cecil B. (Cecil Blount), 1881-1959; Cooper, Courtney Ryley, 1886-1940; Wilstach, Frank Jenners, 1865-1933 (Universal western collection., 2004)
This western interweaves classic real-life old west legends like Wild Bill Hickok, Calamity Jane, Buffalo Bill Cody, George Armstrong Custer and Abraham Lincoln into a stunning tale as vast as the wild frontier itself.